BIBLIOMETRIC ANALYSIS OF AIR POLLUTION'S IMPACT ON CHILDREN WITH ASTHMA: INSIGHTS FROM A DECADE OF RESEARCH (2012-2022) - Ichtiarini Nurullita Santri; Lalu Muhammad Irham; Musfirah Musfirah; Yuniar Wardani; Khoiriyah Isni; Yohane Vincent Abero Phiri; Ahmad Faizal Rangkuti; Nopryan Ekadinata; Wirawan Adikusuma (Universitas Airlangga, 2026)
Introduction: Asthma, a prevalent chronic inflammatory respiratory ailment, affects approximately 8% of children worldwide, with urban air pollution, particularly traffic-related pollutants, recognized as a significant contributor to its incidence. The heightened vulnerability of children due to their immature respiratory and immune systems accentuates the importance of addressing this issue. Aims: This study aims to explore the relationship between air pollution and children with asthma incidence and map the trends. Methods: We conducted a thorough bibliometric analysis, meticulously selecting 4,420 articles from the Scopus database based on specific inclusion criteria. These criteria included papers published between 2012 and 2022, with a particular emphasis on the keywords